Scaling up photoelectrocatalytic reactors: A TiO2 nanotube-coated disc compound reactor effectively degrades acetaminophen - Montenegro-Ayo R. (2019)
Multiple discs coated with hierarchically-organized TiO2 anatase nanotubes served as photoelectrodes in a novel annular photoelectrocatalytic reactor. Electrochemical characterization showed light irradiation enhanced the current response due to photogeneration of charge carriers. The pharmaceutical acetaminophen was used as a representative water micropollutant. The photoelectrocatalysis pseudo-first-order rate constant for acetaminophen was seven orders of magnitude greater than electrocatalytic treatment. Compared against photocatalysis alone, our photoelectrocatalytic reactor at <8 V reduced by two fold, the electric energy per order (EEO; kWh m-3 order-1 for 90% pollutant degradation). Applying a cell potential higher than 8 V detrimentally increased EEO. Acetaminophen was degraded across a range of initial concentrations, but absorbance at higher concentration diminished photon transport, resulting in higher EEO. Extended photoelectrocatalytic reactor operation degraded acetaminophen, which was accompanied by 53% mineralization based upon total organic carbon measurements. This proof of concept for our photoelectrocatalytic reactor demonstrated a strategy to increase photo-active surface area in annular reactors. © 2020 by the authors.